2015
DOI: 10.19182/bft2015.326.a31282
|View full text |Cite
|
Sign up to set email alerts
|

Les Plantes Médicinales De La Région Montagneuse De Kahuzi- Biega en République Démocratique Du Congo : Utilisation, Accessibilité Et Consensus Des Tradipraticiens

Abstract: En ethnobotanique, des aspects comme l’influence de l’accessibilité d’une plante sur sa fréquence d’usage, le consensus entre les tradipraticiens autour des rela- tions maladie-plante ainsi que le degré de fidélité d’une plante à une catégorie de maladies sont essentiels pour évaluer une tradition médicinale ; mais ils sont d’une interprétation difficile. Nous avons exploré ces aspects dans cette étude basée sur des entretiens semi-structurés avec 88 tradi- praticiens issus des communautés Batwa, Havu, Shi et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
5
10
0
4
Order By: Relevance
“…Only 66 species that were identified to species level were taken into consideration for the purpose. The high degree of similarity index in the Congo area was with the study of Shalukoma et al [27], Mangambu, Aluma, et al [25], with JI values of 10.94, 10.38, Balezi et al [20] and Nyakabwa and Dibaluka [ 46], 8.63 respectively. The lowest degree of similarity index was with Bakwaye et al [39] with JI value of 0.88 (Table 6).…”
Section: Jaccard Indexsupporting
confidence: 53%
See 1 more Smart Citation
“…Only 66 species that were identified to species level were taken into consideration for the purpose. The high degree of similarity index in the Congo area was with the study of Shalukoma et al [27], Mangambu, Aluma, et al [25], with JI values of 10.94, 10.38, Balezi et al [20] and Nyakabwa and Dibaluka [ 46], 8.63 respectively. The lowest degree of similarity index was with Bakwaye et al [39] with JI value of 0.88 (Table 6).…”
Section: Jaccard Indexsupporting
confidence: 53%
“…Previous studies have explored medicinal plants in Sud-Kivu over the last two decades [6,[16][17][18][19][20][21][22][23][24][25][26][27][28] However, little is known about ethnobiological researches in Uvira territory and no previous study has surveyed the medicinal plants in plateau and middle plateau of Uvira have been published. Two studies have been carried out in low altitudes of the Uvira territory: Manya et al [29] surveyed anti-malarial herbal of Bukavu and Uvira areas, and Byavu et al [30] focused on ethnoveterinary of cattle.…”
Section: Introductionmentioning
confidence: 99%
“…It makes it possible to assess the relationship between a given plant species and its use by herbalists and/or traditional healers in the treatment of candidiasis [ 49 , 50 ]. The Informant Consensus Factor ( ICF ) calculated by the formula (total number of revenues minus total number of informants / total number of revenues minus 1) [ 49 , 51 , 52 ]. This consensus factor of informants here expresses their “approval rate” in related to the plants used to make the recipes for candidiasis treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The Informant Consensus Factor ( ICF ) calculated by the formula (total number of revenues minus total number of informants / total number of revenues minus 1) [ 49 , 51 , 52 ]. This consensus factor of informants here expresses their “approval rate” in related to the plants used to make the recipes for candidiasis treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In Koupa Matapit the populations reported that some species are becoming rare or extinct, among which are Alchornea cordifolia and Polyscias fulva. None of the both species is mention in the IUCN red list of threatened species; but are listed among useful plants and are mainly used in traditional medicine (Jeruto et al, 2008;Jiofack et al, 2010;Shalukoma et al, 2015). A. cordifolia is frequent in secondary forest and riverine forest; it is especially expended in marshy areas and sometimes in drier sites (Mavar-Manga et al, 2008).…”
Section: Use Of Non-timber Forest Products (Ntfps)mentioning
confidence: 99%